População em situação de rua, transtornos mentais e o uso de álcool e outras drogas: que caminhos seguir? - Tredice, Margareth Arrebola [UNIFESP] (2021)
Purpose: This study aims to understand the diversity of beliefs and attitudes concerning addicted homeless who also have mental health disorders. Method: Qualitative approach was conducted through 26 semi-structured interviews, within a convenience sampling composed by 05 homeless people; 10 mental health and social care workers; 07 addiction and/or mental health specialists; and 03 community leaders. The interviews were submitted to Content Analysis, from the perspective of Bronfenbrenner’s Bioecological Theory. Results: The participants pointed out as the main priority the basic needs provision like housing, water, food and health. The bond with the person assisted emerged as the first step of the care provision, followed by investment in training professionals, creating services more suitable for this population and improving existing services. The professionals from different treatment conceptions did not differ on their perceptions about how to care. Conclusion: Multiple and complex needs may require elementary priority solutions, such as housing and food. The basic needs provision seems to be a convergence point between different ideological conceptions.